Investigation Studies on the Application of Reverberation Time - NOWOŚWIAT, Artur; OLECHOWSKA, Marcelina (Archives of Acoustics, 2016)
The paper presents the research studies carried out on the reverberation time of rooms, in terms of theoretical aspects and applicability potentials. Over the last century a very large number of scientists have been attempting to work out models describing the reverberation time in enclosed rooms. They have also been trying to apply these models for the description of various acoustic parameters of the interior, i.e. the intelligibility of speech, clarity, articulation, etc. In fact, all these models are based on the Sabine’s statistical method. The paper presents the work of the scientists working on this problem, together with prospective applicability potentials. Such a review may be helpful for researchers, designers or architects involved in the discussed subject.